Cannabinoid and nitric oxide signaling interplay in the modulation of hippocampal hyperexcitability: Study on electrophysiological and behavioral models of temporal lobe epilepsy in the rat. (10th September 2015) - Carletti, F.; Gambino, G.; Rizzo, V.; Ferraro, G.; Sardo, P.
Highlights: 7NI and WIN dose-dependently protect from induced epileptiform discharges in MDA. In pilocarpine model 7NI and WIN reduce behavioral seizures dose-relatedly. Pretreatment with 7NI enhances anticonvulsant action of WIN in both models. Involvement of CB1 receptors in 7NI–WIN cross-talk. CB and NO antagonism in the modulation of hyperexcitability in two models of TLE. Abstract: A growing bulk of evidence suggests that cannabinoid system plays a pivotal role in the control of hyperexcitability phenomena. Notwithstanding, the anticonvulsant action of cannabinoids has not been fully addressed, in particular the involvement of potential cellular neuromodulators, for instance nitric oxide. In the current study, we focused on two distinct rat models of temporal lobe epilepsy, the Maximal Dentate Activation and the pilocarpine-induced acute seizures, providing both electrophysiological and behavioral data on cannabinoid and nitrergic system interplay. We evaluated the antiepileptic effects of WIN 55, 212-2, (R)-(+)-[2, 3-dihydro-5-methyl-3-(4-morpholinylmethyl) pyrrolo[1, 2, 3-de]-1, 4-benzoxazin-6-Yl]-1-naphthalenylmethanone (WIN), a CB agonist, and of 7-Nitroindazole (7NI), a preferential neuronal nitric oxide synthase (nNOS) inhibitor, at different doses, alone and in combination. MDA study showed that these drugs protected animals in a dose-dependent manner from electrically induced epileptiform discharges. In pilocarpine model, a dose-related activity of 7NI and WIN: a ) decreased the behavioral scoring, used to describe the severity of chemically induced acute seizures; b ) affected latency of the onset of acute convulsions; c ) dampened mortality rate. Interestingly, the combination of the treatments brought to light that individually ineffective doses of WIN turn into effective when nNOS activity is pharmacologically inhibited in both experimental conditions. This effect is mediated by CB1 receptor since the co-administration of N-(piperidin-1-yl)-5-(4-iodophenyl)-1-(2, 4-dichlorophenyl)-4-methyl-1H-pyrazole-3-carboxamide (AM251), a CB1 receptor specific antagonist, thwarted the 7NI–WIN convergent action. In the light of this, our findings suggest a putative antagonism between CBr-activated pathway and NO signaling in the context of neuronal hyperexcitability and contribute to elucidate possible synaptic processes underlying neuroprotective properties of cannabinoids, with a view to better integrate antiepileptic therapy.